Dokuczliwy skrzyp hermeneutycznego koła – komentarz do artykułu Andrzeja Szahaja - Szajnert, Danuta (Wydawnictwo Naukowe UAM, 2013)
This essay is merely an additional commentary on the article entitled “Hirsch o interpretacji. Analiza krytyczna” (“Hirsch on interpretation. A critical analysis”). I do not focus here on Szahaj’s detailed objections to the concepts proposed by the author of Validity in Interpretation. I concentrate instead on the idea that forms the basis for such objections, i.e. radical, cultural interpretative constructivism. As a skeptical intentionalist, I cannot fully share his opinion and, therefore, I draw attention to views according to which the constructivist paradigm is becoming conventionalized and exhausted (especially in the humanities) and to the possible ways in which it can be overcome.
The annoying creak of the hermeneutic circle – comments on Andrzej Szahaj’s article